PERLINDUNGAN HUKUM TERHADAP EMITEN ATAS CIDERA JANJI PADA PERJANJIAN FULL COMMITMENT - Vunieta . (Jurnal HUKUM BISNIS, 2019)
This research is aimed to find legal certainty through legal protection when there was a full commitment agreement between Underwriter and Issuer, that is breached by Underwriter since not all share had been sold. This research is normative juridical research through a regulatory approach and conceptual approach with the legal problem. Through this research, we will know, when the full commitment agreement has not fulfilled by Underwriter, have legal consequences as a breach of contract which is regulated in Kitab Undang-Undang Hukum Perdata. Therefore, it needs preventive legal effort, to prevent the breach of contract by Underwriter as to the legal protection, through the guarantee of the credibility by renewal permission as Underwriter in every year